Glass and glass production in the Near East during the Iron Age period : evidence from objects, texts and chemical analysis - Schmidt, Katharina (Archaeopress Publishing Ltd, 2019)
This text examines the history of glass in Iron Age Mesopotamia and neighbouring regions (1000-539 BCE). This monograph covers this region and period comprehensively and in detail.